Target‐enrichment sequencing reveals for the first time a well‐resolved phylogeny of the core Bromelioideae (family Bromeliaceae). Issue 1 (28th November 2022) - Bratzel, Fabian; Paule, Juraj; Leebens‐Mack, Jim; Leme, Elton M.C.; Forzza, Rafaela C.; Koch, Marcus A.; Heller, Sascha; Zizka, Georg
Abstract: A phylogenomic analysis of the so far phylogenetically unresolved subfamily Bromelioideae (Bromeliaceae) was performed to infer species relationships as the basis for future taxonomic treatment, stabilization of generic concept, and further analyses of evolution and biogeography of the subfamily. A target‐enrichment approach was chosen, using the Angiosperms353 v.4 kit RNA‐baits and including 86 Bromelioideae species representing previously identified major evolutionary lineages. Phylogenetic analyses were based on 125 target nuclear loci, assembled off‐target plastome as well as mitogenome reads. A Bromelioideae phylogeny with a mostly well‐resolved backbone is provided based on nuclear (194 kbp), plastome (109 kbp), and mitogenome data (34 kbp). For the nuclear markers, a coalescent‐based analysis of single‐locus gene trees was performed as well as a supermatrix analysis of concatenated gene alignments. Nuclear and plastome datasets provide well‐resolved trees, which showed only minor topological incongruences. The mitogenome tree is not sufficiently resolved. A total of 26 well‐supported clades were identified. The genera Aechmea, Canistrum, Hohenbergia, Neoregelia, and Quesnelia were revealed polyphyletic. In core Bromelioideae, Acanthostachys is sister to the remainder. Among the 26 recognized clades, 12 correspond with currently employed taxonomic concepts. Hence, the presented phylogenetic framework will serve as an important basis for future taxonomic revisions as well as to better understand the evolutionary drivers and processes in this exciting subfamily.